Predominant mesangial IgM, C3, and λ light chain depositions and interstitial nephritis in a patient with overlap syndrome and positivity for anti-mitochondrial M2 antibody: a case report. Issue 1 (11th August 2021) - Yamada, Saeko; Kanda, Hiroko; Abe, Hiroyuki; Domoto, Yukako Shintani; Yoshida, Ryochi; Harada, Hiroaki; Kubo, Kanae; Ushiku, Tetsuo; Fujio, Keishi
ABSTRACT: Overlap syndrome refers to a group of conditions that have clinical features of more than one well-characterised rheumatic disease and meet the respective classification criteria. There are no typical renal histological findings in overlap syndrome. When patients with overlap syndrome develop renal dysfunction, various potential causes, including lupus nephritis (LN), renal crisis by systemic sclerosis, interstitial nephritis, and so on, need to be distinguished. Here, we report a 44-year-old woman with overlap syndrome involving systemic lupus erythematosus (SLE), diffuse cutaneous systemic scleroderma, and Sjogren's syndrome, who was also positive for anti-mitochondrial M2 antibody. She developed glomerular haematuria, proteinuria, and increase in creatinine appeared gradually. Suspecting LN, renal biopsy was performed. However, in the interstitium, mild infiltration of lymphocytes and plasma cells and very partial fibrosis were observed. Immunofluorescence microscopy revealed predominant mesangial immunoglobulin M, C3, and λ light chain staining. Overall, LN was not diagnosed based on these findings. Renal dysfunction was normalised by glucocorticoid treatment for 3 months. This case suggests the importance of a renal diagnosis based on renal pathological findings, especially in a case of overlap syndrome including SLE.